Discourse Markers as Turn-Transition Devices: Evidence From Speech and Instant Messaging. Issue 1 (2nd January 2018) - Degand, Liesbeth; van Bergen, Geertje
Abstract : In this article we investigate the relation between discourse markers and turn-transition strategies in face-to-face conversations and Instant Messaging (IM), that is, unplanned, real-time, text-based, computer-mediated communication. By means of a quantitative corpus study of utterances containing a discourse marker, we show that utterance-final discourse markers are used more often in IM than in face-to-face conversations. Moreover, utterance-final discourse markers are shown to occur more often at points of turn-transition compared with points of turn-maintenance in both types of conversation. From our results we conclude that the discourse markers in utterance-final position can function as a turn-transition mechanism, signaling that the turn is over and the floor is open to the hearer. We argue that this linguistic turn-taking strategy is essentially similar in face-to-face and IM communication. Our results add to the evidence that communication in IM is more like speech than like writing.